Heat-flux Instabilities of Regularized Kappa Distributed Strahl Electrons Resolved with ALPS - Dustin L. Schröder; Marian Lazar; Rodrigo A. López; Horst Fichtner (The Astrophysical Journal)
The fluid behavior of the solar wind is affected by the heat flux carried by the suprathermal electron populations, especially the electron strahl (or beam) that propagates along the magnetic field. In turn, the electron strahl cannot be stable, and in the absence of collisions, its properties are regulated mainly by self-generated instabilities. This paper approaches the description of these heat-flux instabilities in a novel manner using regularized Kappa distributions (RKDs) to characterize the electron strahl. RKDs conform to the velocity distributions with suprathermal tails observed in situ, and at the same time allow for consistent macromodeling, based on their singularity-free moments. In contrast, the complexity of RKD models makes the analytical kinetic formalism complicated and still inaccessible, and therefore, here heat-flux instabilities are resolved using the advanced solver ALPS. Two primary types of instabilities emerge depending on plasma conditions: the whistler and firehose heat-flux instabilities. The solver is successfully tested for the first time for such instabilities by comparison with previous results for standard distributions, such as Maxwellian and Kappa. Moreover, the new RKD results show that idealized Maxwellian models can overrate or underestimate the effects of these instabilities, and also show differences from those obtained for the standard Kappa, which, for instance, underestimate the firehose heat-flux growth rates.